Operations management practices for hostels paulistanos success (Research, Society and Development, 2020)
The increase in foreign tourism reflected in the greater diversification of lodging facilities in the city of São Paulo. Among these facilities, the hostel presents itself as an economical tourist option and serves mainly a young portion of these foreign tourists. In this way, the planning and control of operations at hostels become management tools to better serve the tourist. This work proposes a qualitative analysis with an exploratory and descriptive approach, in order to draw a current panorama of São Paulo hostels. The results showed that effective planning of operations, as well as differential hospitality, can provide accessibility in the city and provide a greater number of national and international tourists, who seek a harmonious environment and interpersonal experiences, which promotes more cultural exchanges, as well as encouragement for the city to become more pleasant amid an ultra urbanized and listless environment. It is noticed that the hostels in question use the most up-to-date information regarding the management of their operations for the purpose of customer loyalty, without losing the characteristic of a hostel, which is to be a welcoming environment, in which it is possible exchange unique experiences, such as: culture and empathy, for example.